COMPARATIVE ANALYSIS OF DIGITAL PDCTABILIZERS OF MOBILE OBJECTS WITH LOWFREQUENCY BUTTERWORT AND LANCZOS FILTERS - Aleksandrova, T. E.; Kononenko, V. A.; Lazarenko, A. A.; Zein, Ali (Radio Electronics, Computer Science, Control, 2012)
The problem of constructing a digital PD-stabilizers of mobile objects with noise input signals is discussed . The comparative analysis of the stabilizers with Butterwort and Lanczos filters of the various orders is considered.